Para mayor satisfacción (de): plurifunctional connective expression, support and deterrence - Cucatto, Mariana (Círculo de Lingüística Aplicada a la Comunicación, 2021)
By means of the expression para mayor satisfacción (de), justices announce in their judgments that they will introduce more arguments, which are not used to found the decision, in order to further and better respond to the requests and defenses put forward by the parties. On this particular occasion, we are going to study the persuasive power that these reasons introduced by the phrase para mayor satisfacción (de) have in the judgments delivered by the Supreme Court of the Province of Buenos Aires (Argentina). In this respect, we show that para mayor satisfacción (de) is a connective device which allows justices to establish: 1) complex –and iconic– interpretation links, as it fulfills a triple connective function: contrast + addition + closure; and 2) various “addressing degrees”, since it establishes a graded form of address used to directly deter the appellant and make such party change its thoughts or acts, as well as indirectly deter the appellee and, more remotely still, any other addressees, so as to warn them against the possible negative effects of not following this Court’s position.